Analytical review of the catalytic cracking of methane. (15th September 2022) - Hamdan, Mohammad; Halawy, Layal; Abdel Karim Aramouni, Nicolas; Ahmad, Mohammad N.; Zeaiter, Joseph
Highlights: Activity-stability tradeoff when using irreducible metal oxide supports. Zeolites improve active metal dispersion and formation of carbon nanofibers. Ni-Cu catalysts enhances methane chemisorption and growth of carbon nano-filaments. Cerium enhances metal-support interactions and prevents sintering. Zinc promoters prevent formation of NiAl2 O4 spinel structures. Abstract: Catalytic decomposition of methane (CDM) is a low-carbon hydrogen production process where pure hydrogen and solid carbon are produced. In this study, we investigate catalyst performance in terms of active metals, metal supports, and promoters. These structures are known to strongly influence catalyst activity and stability; where the former is dependent on the size of the formed active metal particles, along with the intensity of their interactions with the support; and the latter is contingent on the equilibrium between the rates of decomposition and diffusion of methane. Carbonaceous catalysts exhibit lower activity compared to metallic catalysts, and result in the formation of economically unfavorable amorphous carbon as opposed to the more profitable carbon filaments or nanotubes. Irreducible metal oxides and specific zeolites have shown promising results when used as supports for nickel-based catalysts, especially when coupled with special metallic promoters to either enhance metal-support interactions, or to increase the carbon diffusion rates and enhance the carbon capacity of the catalyst. The metal-support interactions attained within the catalyst should not be too weak as to cause rapid sintering of the active metal, nor too intense as to lead to the formation of spinel structures or solid solutions which are detrimental to catalyst activity. Exploiting the synergic effects of bi- and tri-metallic catalysts is essential in designing a potential catalyst which possesses high activity and stability at moderate operating temperatures.